Pain Control by Nerve Block in Herpes Zoster - Ahmed, Hiwa Omer; Bichkol, Niaz Ahmed (Sulaimani Journal for Pure and Applied Sciences, 2001)
Herpes zoster is one of the common viral diseases in our locality, it is characterized by fever, skin eruptions and pain in the course of the affected nerve. The pain is moderate to severe, burning or stabbing in nature, persistent, radiating over the distribution of the affected nerve. Many drugs & therapeutic procedures have been advocated in the control of this exhausting pain, with equivocal results. In the present work we used simple, easy, cheap and tolerable procedure with a reasonable result in comparison with the current modalities of the treatment.
Keywords: PainControulHerpes Zoter Nerve Block